Skin Changes Associated with Pregnancy: Insights from a Tertiary Care Hospital - Neha Shukla; Himanshy Rai; Pragati Sharma; Parul Nema (Journal of Pharmacy and Bioallied Sciences)
Background: Pregnancy induces significant physiological and hormonal changes in women, predisposing them to various dermatological manifestations. This study aimed to evaluate the prevalence and patterns of pregnancy-related changes in the skin. Methods: A cross-sectional investigation was carried out on 445 expectant mothers attending an Indian tertiary medical center’s outpatient department. Results: The most frequent physiological alterations were pigmentary changes, with secondary areola changes being the most frequent, followed by lineanigra. Vascular changes, primarily non-pitting pedal edema, were also noted. Connective tissue changes were dominated by striae gravidarum. Among pregnancy-specific dermatoses, atopic eruptions were the most frequent, followed by intrahepatic cholestasis. Infections with fungi were the most common among study participants. Conclusion: Dermatological manifestations during pregnancy are common and exhibit a wide spectrum of changes, including specific patterns. Accurate identification and appropriate management of these conditions are essential to optimize maternal and fetal outcomes.